2016
DOI: 10.1007/s00520-016-3200-8
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the seasons of cancer survivorship: mind-body therapy use and reported reasons and outcomes by stages of cancer survivorship

Abstract: Purpose Mind-body therapies (MBT), a subset of complementary and alternative medicine (CAM), are used by cancer survivors to manage symptoms related to their cancer experience. MBT use may differ by cancer survivorship stage (i.e., acute, short-term, long-term) because each stage presents varying intensities of medical activities, associated emotions, and treatment effects. We examined the relationship between MBT use and survivorship stage (acute: <1 year; short-term: 1 to 5 years; long-term: >5 years since d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…Overall, the use of MBM in patients with cancer appears to be increasing. When examining the data from the Adult Alternative Health/Complementary and Alternative Medicine supplement to the 2012 NHIS, approximately 8.3% to 15.4% of patients with cancer reported using mind‐body therapies . In the current NHIS data, approximately 27.6% of patients with cancer who experienced sleep problems and 17.9% of patients with cancer without sleep problems used MBM.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Overall, the use of MBM in patients with cancer appears to be increasing. When examining the data from the Adult Alternative Health/Complementary and Alternative Medicine supplement to the 2012 NHIS, approximately 8.3% to 15.4% of patients with cancer reported using mind‐body therapies . In the current NHIS data, approximately 27.6% of patients with cancer who experienced sleep problems and 17.9% of patients with cancer without sleep problems used MBM.…”
Section: Discussionmentioning
confidence: 87%
“…Analyses by Campo et al have suggested that disease prevention is another reason for the practice of MBM. The authors examined data from the Adult Alternative Health/Complementary and Alternative Medicine supplement to the 2012 NHIS regarding reported reasons for and outcomes of MBM use .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations